The molecular mechanism of solvent cryoprotection - Mandumpal, Jestin Baby (Curtin University, 2011)
The cryopreservation of animal and human cells, tissues and organs as well as germplasm of endangered plant species is a key area in contemporary biotechnology. In this thesis, certain classes of chemicals known as cryoprotective agents (CPA) are investigated in detail. The structural, dynamic and vitrification properties of representative CPAs are studied using the state-of-the art molecular dynamics simulation techniques. The simulations provide a rationale at the molecular level of the cryoprotective properties of aqueous solutions of compounds such as DMSO, methanol and ethanol.This is a brief synopsis of the thesis:CHAPTER 1. This chapter provides a general introduction of various aspects of cryoprotection. A brief overview of the challenges that are encountered in the cryopreservation protocol is given, followed by a list of known cryoprotectants. Next various mechanisms to account for cryopreservation have been explained in detail. This section is followed by one of the important theme of this thesis, vitrification, and finally water and its properties.CHAPTER 2. This chapter discusses the theoretical background of molecular dynamics simulations and various analyses, and a brief overview of water forcefields.CHAPTER 3. Molecular dynamics simulations of DMSO in water elucidating its structural, dynamic and hydrogen bonding properties are described in this chapter. Comparison with its chemical analogue, Acetone, is made in an attempt to rationalise DMSO‟s exceptional properties in a wide range of temperatures.CHAPTER 4. Structural and hydrogen bonding properties of aqueous ethanol and methanol solutions have been described in this chapter.CHAPTER 5. Estimation of glass transition temperatures of aqueous mixtures of DMSO, acetone, ethanol, methanol and water using simulated annealing molecular dynamics techniques has been described in this chapter.CHAPTER 6. Important conclusions arising from this study and scope of the work have been summarised in this chapter.